PENGEMBANGAN SUMBERDAYA MANUSIA LANGKAH MENUJU INVESTASI SDM - Rahayu, Amy Y.S. (FIA UB, 2007)
Globalization and free market oriented have big implication on public sectors to raise quality and professional of their man source. And it need full sensitivity of public institution. Man is people employed assets who have different values, competency, skill, knowledge and personal behavior Human Resource Development is knowledge, skill, competency and performance improvement continuously in doing their tasks and responsibilities. The capacity of organization to develop their human resource will put them in each level of organization types (Traditional Organization, Learning Organization and Developmental Organization).Keywords: Traditional Organization, Learning Organization, Developmental Organization, Human Resources Development.